Pengembangan Aplikasi Pemantauan Tingkat Kebahagiaan Sumber Daya Manusia Kesehatan Berbasis Android - Akhdan Navin Naeem; Riswal Hanafi Siregar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The level of happiness among human resources (HR) in the healthcare sector plays a crucial role in supporting performance and service quality. However, efforts to monitor HR happiness have not yet been carried out regularly or in a measurable way. This study aims to develop an Android-based application for monitoring the happiness levels of healthcare HR, enabling periodic and real-time reporting of emotional conditions. The software development method used is Extreme Programming (XP), which emphasizes rapid user feedback and short, adaptive development iterations. The development process includes planning, design, coding, and testing stages conducted iteratively based on user input. The application provides features such as daily happiness logging, data visualization in graphical form, and a notification system. Black-box testing results indicate that all features function as intended. Initial trials with several healthcare workers show that the application is easy to use and helps in expressing daily happiness conditions. Through this application, healthcare institutions can systematically obtain HR happiness data as a basis for policymaking aimed at improving workplace well-being.